Antimicrobials and antimicrobial resistance - Lyons, Kevin (2018)
The emergence and spread of molecular mechanisms which make bacteria resistant to antibiotics together constitute a significant threat to human health which is global and growing. Two research projects with implications for the understanding of bacterial pathogenicity and antibiotic resistance are presented here. Both projects concern gene regulation in Gram-negative bacteria, and originated from data sets acquired via genome-wide investigations: a ChIP-seq data set and an RNA-seq data set respectively. Results obtained in the first project suggest a negative role for the transcription factor MarA in Escherichia coli biofilm formation, through transcriptional activation of the ycgZ-ymgA-ariR-ymgC operon; whereas results from the second project suggest that a newly-identified sRNA in Pseudomonas aeruginosa binds to the post-transcriptional regulators RsmA and RsmN, potentially promoting the chronic infection lifestyle which is associated with biofilm formation. The relevance of both projects to the problem of antibiotic resistance stems in part from their association with systems capable of regulating the formation of biofilms. Biofilms are formed when communities of microbes attach to surfaces via a self-produced matrix of hydrated extracellular polymeric substances such as polysaccharides, proteins, nucleic acids and lipids. They are typically associated with an inherent increase in resistance to antibiotics and other molecules, and are associated with ~65–80% of all bacterial infections in humans. Understanding these structures, and devising strategies to disrupt them and/or prevent their formation is highly desirable, as they can have implications not only for human health, but also for the efficiency and safety of industrial processes, waste management and food production.